Perbedaan Kadar LDL Pada Penderita Diabetes Melitus Tipe 2 Dengan Penyakit Jantung Koroner Dan Tanpa Penyakit Jantung Koroner Di RSUD Dr. Moewardi - Puspaningrum, Citra, dr. Iin Novita Nurhidayati Mahmuda, M.Sc, Sp.PD (2017)
Background: Coronary Heart Disease (CHD) is one of cardiovascular disease (heart disease and vessels disease) which main cause of death in the world. CHD be caused commond mortality and morbidity in the type 2 diabetes mellitus (DM). Increasing LDL levels are a major risk factor for CHD. Objective: To know the distinction of LDL levels in type 2 diabetes mellitus patients with CHD and without CHD in Dr. Moewardi Hospitals Surakarta. Methods: An observational analytic research with cross sectional study design. Subjects were type 2 diabetes mellitus patients with CHD and without CHD in Dr. Moewardi Hospitals. The sampling performed in non-probability sampling with purposive sampling technique. Data were obtained from medical records of patients from September 2015 to September 2016. Statistical analysis used independent T test. Results: This study used 70 sample, consists of 35 patients in the group of type 2 diabetes mellitus with CHD and 35 patients in the group of type 2 diabetes mellitus without CHD. The difference between the mean levels of LDL in type 2 diabetes mellitus with CHD group 130,54 ± 40,569 mg/dl compared with type 2 diabetes mellitus without CHD group 95,77 ± 29,289 mg/dl with p=0,000. Conclusions: There was distinction of LDL levels in type 2 diabetes mellitus patients with CHD and without CHD.